Pembuatan Teh Bawang Dayak dan Manfaatnya Bagi Kader Pusat Kesehatan Masyarakat Harapan Baru Samarinda Seberang - Annaas Budi Setyawan; Arief Budiman; Taufik Septiawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The community service activity was attended by cadres of Harapan Baru Community Health Center (Puskesmas) Samarinda Seberang who participated at the bawang dayak tea making program from the beginning to the end of the event, besides that in this activity also provided health education to the cadres about high blood pressure and even diabetes. This activity has the primary purpose of inviting Puskesmas cadres to utilize natural plant products bawang dayak, which can be processed into tea and can be taken for health benefits and have economic value. In using this bawang dayak plant, it needs proper processing so that the content is not reduced. The first step is to cut roots and leaves from bawang dayak, then wash them in running water, then slice them in a slice and then dry them, before finally storing them in airtight containers. Utilization of bawang dayak which are then processed into tea, this means encouraging the use of Borneo's unique plants into an alternative source of health and the ability to handle these plants into a product means increasing economic opportunities to contribute to solving social problems.